Plato’s Socrates, Sophistic Antithesis and Scepticism - Blyth, Dougal (PLATO JOURNAL, 2019)
In some Platonic dialogues Socrates apparently shares significant characteristics with contemporary sophists, especially a technique of antithetical argumentation. Since sophists anticipated later Academic philosophers in arguing antithetically and a resultant form of, then, with Socrates’ repeated claims to ignorance, Plato’s depiction of him arguing antithetically suggests later Academics could plausibly appeal to Plato for evidence that Socrates and he were, as it seems they actually did.